The Birth of Joint-Stock Banking: England and New England Compared - Newton, Lucy (Business History Review, 2010)
By the end of the nineteenth century, the banking systems of England and New England were very different. England possessed a small number of large-scale clearing banks that had established extensive branch networks and dominated the domestic market. In contrast, New England banking was characterized by a large number of small-scale institutions. Yet, a century earlier, there were striking similarities between the two systems. An analysis of their evolution over the course of the nineteenth century provides an international and comparative perspective on the continuing debate over banking institutions, lending patterns, and economic growth.
Keywords: Business History and gender